Sequence-dependent Internalization of Aggregating Peptides - Couceiro, José R. (J Biol Chem, 2015)
Recently, a number of aggregation disease polypeptides have been shown to spread from cell to cell, thereby displaying prionoid behavior. Studying aggregate internalization, however, is often hampered by the complex kinetics of the aggregation process, resulting in the concomitant uptake of aggregates of different sizes by competing mechanisms, which makes it difficult to isolate pathway-specific responses to aggregates. We designed synthetic aggregating peptides bearing different aggregation propensities with the aim of producing modes of uptake that are sufficiently distinct to differentially analyze the cellular response to internalization. We found that small acidic aggregates (≤500 nm in diameter) were taken up by nonspecific endocytosis as part of the fluid phase and traveled through the endosomal compartment to lysosomes. By contrast, bigger basic aggregates (>1 μm) were taken up through a mechanism dependent on cytoskeletal reorganization and membrane remodeling with the morphological hallmarks of phagocytosis. Importantly, the properties of these aggregates determined not only the mechanism of internalization but also the involvement of the proteostatic machinery (the assembly of interconnected networks that control the biogenesis, folding, trafficking, and degradation of proteins) in the process; whereas the internalization of small acidic aggregates is HSF1-independent, the uptake of larger basic aggregates was HSF1-dependent, requiring Hsp70. Our results show that the biophysical properties of aggregates determine both their mechanism of internalization and proteostatic response. It remains to be seen whether these differences in cellular response contribute to the particular role of specific aggregated proteins in disease.